The Relationship Of Knowledge And Attitude Of Mother’s Breasfeeding With Exclusive Giving - Monifa Putri; Deni Listi (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2020)
Breast milk (ASI) is the only food that is the best for babies, because it has themost complete nutritionalcomposition for baby’s growth and development.Methode: this research is analytic using cross sectional approach. The samplingtechnique is by simple random sampling. Data analysis was performed using theChi-Square test at a significance level of p<0.05. Result: the study showed thatfrom 68 respondents the majority of knowledge of breastfeeding morthers withexclusive breastfeeding was well-informed 48 people (70.6%) and the ChiSquare statistical test results obtained a P value of <0.05 (P. Value = 0.004).Breastfeeding with exclusive breastfeeding the majority of positive attitude 57people (83.8%) and the Chi-Square statistical test results obtained a value ofP<0.05 (P. Value=0.008). Conclusion: based on the results of the study showeda significant relationship between knowledge (P. Value=0.004) and attitude (P.Value=0.008) towards exclusive breastfeeding.